Latching-Declutching Control of Wave Energy Converters Using Derivative-Free Optimization - Feng,Z; Kerrigan,EC (IEEE Transactions on Sustainable Energy, 2015)
We consider predictive control of a wave energy converter(WEC) that can switch between three modes: 1) powergeneration; 2) declutched with no power generation; or 3) latchedwith zero velocity. We propose a formulation that turns the optimalcontrol problem into a small dimensional discrete optimizationproblem, where the only decision variables are bounds onthe latching time and power take-off (PTO) time, whereas theobjective function is computed from the trajectory of a hybridsystem with linear dynamics in each sample interval. The optimizationproblem is solved using a novel derivative-free algorithmthat exploits the quantization of the decision variables in orderto reduce the number of function evaluations. Two closed-loopformulations are also studied within a receding horizon implementation:the first one uses past wave information and can double theenergy generation compared to the uncontrolled case, while thesecond formulation uses predictions of future waves and is able toresult in a further increase in energy generation. The benefits ofcodesigning the physical system and controller is compared to thesequential approach of first optimizing the physical system withoutcontrol, followed by controller design.